2011
DOI: 10.1364/oe.19.010443
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Raman soliton during supercontinuum generation near the zero-dispersion wavelength of optical fibers

Abstract: Abstract:We observe unique dynamics of Raman soliton during supercontinuum process when an input pulse experiences initially normal group-velocity dispersion with a negative dispersion slope. In this situation, the blue components of the spectrum form a Raman soliton that moves faster than the input pulse and eventually decelerates because of Ramaninduced frequency downshifting. In the time domain, the soliton trajectory bends and becomes vertical when the Raman shift ceases to occur as the spectrum of Raman s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Fundamentally the dynamics of supercontinuum generation process comes from the pivotal role played by the interaction between higher-order dispersion and nonlinearity when ultrashort optical pulses are launched in the anomalous group-velocity dispersion domain. The phenomenon which involves the dynamics of several solitons and dispersive waves (radiations) in photonic crystal fibers has attracted considerable attention since its wide applications ranging from spectroscopy, metrology, telecommunications [30][31][32][33][34][35][36] and the dynamics of Raman soliton [37]. Besides, the influence of the simultaneous action of higher-order effects including intra-pulse Raman scattering, higher-order dispersion, self steepening or quintic nonlinearity, to describes the propagation of ultrashort pulses in optical fibers has been extensively studied by many authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamentally the dynamics of supercontinuum generation process comes from the pivotal role played by the interaction between higher-order dispersion and nonlinearity when ultrashort optical pulses are launched in the anomalous group-velocity dispersion domain. The phenomenon which involves the dynamics of several solitons and dispersive waves (radiations) in photonic crystal fibers has attracted considerable attention since its wide applications ranging from spectroscopy, metrology, telecommunications [30][31][32][33][34][35][36] and the dynamics of Raman soliton [37]. Besides, the influence of the simultaneous action of higher-order effects including intra-pulse Raman scattering, higher-order dispersion, self steepening or quintic nonlinearity, to describes the propagation of ultrashort pulses in optical fibers has been extensively studied by many authors.…”
Section: Introductionmentioning
confidence: 99%
“…However some methods of analysis and the range of applicability used until now have as common focal points the supercontinuum generation, the exploitation of the soliton self-frequency shift in the realization of pulsed wavelength tunable sources, its cancelation by resonant emission of normally dispersive waves, the enhancement or the soliton self-frequency shift performance in highly nonlinear chalcogenide, as well as other nonlinear processing applications and the well-known physical concept effect named group-acceleration mismatch [30][31][32][33][34][35][36][37][38][39][40]. However, if the efficient practical method to calculate the soliton self-frequency shift uses the method of moment [20][21][22], it is also observed that some physical specific pulse parameters able to give a qualitative detailed picture of the role and mode of singular or simultaneous action of some selected higher-order terms (such as third-order dispersion, self-phase modulation, quintic nonlinearity, self-steepening, or stimulated Raman scattering) require an important amount of calculation with these method using the exact pulse field throughout the pulse propagation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a highly nonlinear fiber (HNLF) or photonic crystal fiber (PCF) must be used for supercontinuum generation. Previous studies have shown that there are four main physical process that are responsible for the supercontinuum generation, such as self-phase modulation (SPM), stimulated Raman scattering (SRS), self-steepening (SS) [79] and dispersive wave (DW) generation (which is also called non-solitonic radiation) [80]. Generally, the long-wavelength edge spectral broadening can be attributed to Raman scattering self-frequency shift [81], while the short-wavelength edge spectral broadening originates from the dispersive wave generation.…”
Section: Supercontinuum Generationmentioning
confidence: 99%
“…The effect of XPM on Raman solitons was investigated in Ref. [20], and the shift was shown to depend on the dispersion slope of the fiber. Two-color pulse collisions were also studied as event horizon analogies [21][22][23] and for making an all-optical transistor [24].…”
Section: Introductionmentioning
confidence: 99%